RISK IN CYBER ENVIRONMENT - J. Aleksovski; N. Pirovski; I. Georgieva (Trakia Journal of Sciences)
Introduction: Cyber environment is a new type of interaction media that implies a modification of existing risks and a new type of risks, covered by an instrument for risk evaluation. Materials and methods: Existing risk evaluation instruments, psychology risk questionnaires and cyber risks categories. Results: Instrument for cyber risk evaluation with а specific modifications of the existing physical and psychological risks and the new type: cyber risks. Discussion: Cyber environment is new, yet already widely used and powerful. This creates an opportunity for improved functionality, but also for increased risk. Conclusion: The risk of using cyber environment is not limited to the field of information. It is a complex, personal, bio-psycho-social risk with daily and mass exposure and diverse consequences. Its assessment is difficult and currently inadequate in the direction of underestimation.